The Role of Stakeholders in The Development of Pringgasela Tourism Village East Lombok Regency - Dyah Estu Larasati; I Gusti Ngurah Widyatmaja; Yayu Indrawati (Cita Konsultindo Research Center, 2024)
The study aims to identify the conditions under which tourism exists and analyze the role of tourism stakeholders in the Pringgasela Tourism Village. We use a qualitative-descriptive approach, accessing the data sources through direct observations, in-depth interviews, and documentation. The data analysis process employs data reduction techniques throughout the stages of collection, verification, and conclusion drawing. The research shows that Pringgasela Tourism Village has a lot of potential. This is clear from looking at component (5A) attractions, activities, accommodations, amenities, and accessibility in its development, which also made the roles of everyone involved stronger. Therefore, the development of Pringgasela Tourism Village as a tourist destination holds significant potential to enhance the community's economy and well-being, as well as draw in more tourists.